Financial Crisis and Economic Restructuring in Southeast Asia - Yul Kwon (East Asian Economic Review, 1998)
The hidden inner structural problem with the rapid growth of economy was exposed after the financial crisis and South-East Asia is facing serious economic crisis. Currently, the core of the financial crisis is the low function of financial system, so to make the financial department normal by rebuilding the untrue financial system is the problem we are facing. If our financial sector delay the structural adjustment and continue to be competitive in credit, the insolvent debenture will soar. Enterprise and financial institute closed one after another, causing economic collapse and the vicious circle. Accordingly, in order to overcome the current South-East Asia financial crisis, countries there put their focus on the rebuilding of financial system and under the financial system of IMF (International Monetary Foundation), they are doing economic adjustment in large-scale. This thesis studied the nature and features of the Asian financial crisis, and analyzed the main direction and feature of financial policy under IMF. Especially it analyzed the current situation in different countries for this adjustment, and researched the result of the economical reform after this financial crisis.